Tradução e adaptação transcultural do domínio fadiga do patient-reported-outcomes measurement information system promis® para a língua portuguesa - Alves, Flávio Sérgio Marques (2013)
The National Institute of Health (NIH) North American released in 2004, a large item bank with the promise of innovation studies and evaluations of results reported by Patient- Reported-Outcomes (PROs) for people with chronic diseases, can be considered as a new promising assessment of health-related quality of life (HRQoL). This new evaluation system was called Patient-Reported-Outcomes Measurement Information System (PROMIS®) and is divided into banks of items where each evaluates a domain. Among the top five item banks developed initially by PROMIS® is the items bank Fatigue domain. There is still no consensus on the definition of this symptom present in many chronic diseases. This study aimed to translate and cross-culturally adapt to the Brazilian population the 82 items of this domain. The translation and cross-cultural adaptation followed a strict protocol translation and back translation. The translated version was pre-tested on a sample of 20 Brazilian recruited at the Hospital Clinics of Universidade Federal de Uberlândia, who responded to a brief cognitive interview and retrospective questionnaire in order to test the conceptual, cultural and semantics of items. Few differences were found in the process of translation and back translation. Only three of the 82 items had to be rewritten due to inappropriate content culturally. The pretest showed that in general, the items were translated into Portuguese language understanding, and that only four items needed to be rewritten, but with no change and conceptual semantics. The results show that the translated version of the item bank Fatigue PROMIS® is conceptual, cultural and semantically equivalent to its original version.